Nonlinear Radiative Effects on MHD Flow Past a Nonlinearly Stretching Surface Embedded in a Porous Medium - Gururaj, A. David Maxim; Devi, S.P. Anjali (Journal of Informatics and Mathematical Sciences, 2017)
An analysis has been carried out to investigate the steady, laminar, two dimensional hydromagnetic flows with heat transfer of an incompressible, viscous and electrically conducting fluid over a surface stretching with a power-law velocity distribution and embedded in a porous medium in the presence of a variable magnetic field. The radiative heat flux term is taken to be nonlinear using Rosseland diffusion approximation. Governing nonlinear partial differential equations are transformed to nonlinear ordinary differential equations by utilizing suitable similarity transformation. Then the resulting nonlinear ordinary differential equations are solved numerically using Fourth-Order Runge-Kutta based shooting method along with Nachtsheim-Swigert iteration scheme for satisfaction of asymptotic boundary conditions and the numerical results for velocity and temperature distribution are obtained for different values of radiation parameter, permeability, velocity exponent parameter, surface temperature parameter, magnetic interaction parameter and Prandtl number. The dimensionless rates of heat transfer and skin friction coefficient are also obtained for different physical parameters and are presented graphically.